Pre-Radiation dental considerations and management for head and neck cancer patients. (January 2018) - Kufta, Kenneth; Forman, Michael; Swisher-McClure, Samuel; Sollecito, Thomas P.; Panchal, Neeraj
Highlights: There is lack of evidence-based dental treatment guidelines for head and neck radiation patients. Dental management organized into 3 categories: cancer, patient, and dentition. This review provides individualized guidelines for treating these patients. Abstract: Treatment of head and neck cancer (HNC) is accompanied by a high rate of morbidity, and complications can have a lifelong, profound impact on both patients and caregivers. Radiation-related injury to the hard and soft tissue of the head and neck can significantly decrease patients' quality of life. The purpose of this study is to provide patent-specific guidelines for managing the oral health and related side effects of HNC patients treated with radiation therapy. Based on reviewed articles retrieved on the PubMed database, guidelines for management of the oral health of this patient population were organized into three separate categories: cancer, patient, and dentition. The location, type, and staging of the cancer, along with the radiation used to treat the cancer significantly impact dental treatment. Several unique patient characteristics such as motivation, presence of support system, socioeconomic status, nutrition, and race have all been found to affect outcomes. Dental disease and available supportive dental management was found to significantly impact treatment and quality of life in this patient population. By comprehensively assessing unique cancer, patient, and dental-related factors, this review provides individualized evidence-based guidelines on the proper management of this complex and vulnerable patient population.